2017
DOI: 10.1002/2016jb013789
|View full text |Cite
|
Sign up to set email alerts
|

The effect of speleothem surface slope on the remanent magnetic inclination

Abstract: Speleothems are of interest for high‐resolution reconstruction of the Earth's magnetic field. However, little is known about the influence of speleothem morphologies on their natural remanent magnetization (NRM) record. Here we report on a high‐resolution paleomagnetic study of a dome‐shaped speleothem of middle Holocene age from southern Portugal, with special attention to the anisotropy of magnetic susceptibility (AMS) and anisotropy of anhysteretic remanent magnetization (AARM). To assess the potential infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 40 publications
1
36
0
2
Order By: Relevance
“…Lava flow and archeological artifacts record a thermal remanent magnetization of the last time they cooled below Curie temperature, which is generally more stable than sediment magnetization. In a previous study (Ponte et al, 2017), we have demonstrated that magnetic PONTE ET AL. More recently, speleothems have been explored as potential archives of the Earth's magnetic field.…”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…Lava flow and archeological artifacts record a thermal remanent magnetization of the last time they cooled below Curie temperature, which is generally more stable than sediment magnetization. In a previous study (Ponte et al, 2017), we have demonstrated that magnetic PONTE ET AL. More recently, speleothems have been explored as potential archives of the Earth's magnetic field.…”
Section: Introductionmentioning
confidence: 83%
“…Osete et al (2012) reported the first relative paleointensity (RPI) record in a speleothem from Cobre Cave in northern Spain and recognized the previously reported low RPI values of the Blake geomagnetic excursion, with a notable relative maximum peak just after the first reversal. Here we report on additional directional (PSV) data in a radioisotopic well-dated speleothem (named SPAIV; dated 4,500-3,200 years BCE by the U-Th method) collected in Algarve (Portugal), previously studied by Font et al (2014) and Ponte et al (2017), and compared them with contemporaneous archaeomagnetic, volcanic, and speleothem data from Spain and Italy, as well as three different PSV models (CALS10k.1b, SHA.DIF.14k, and pfm9k.1a). In front of these recent advances in the field of speleothem magnetism, further examination of their reliability as time series recorders of paleosecular variations (PSVs) and paleointensity is needed.…”
Section: 1029/2018gc007651mentioning
confidence: 99%
See 3 more Smart Citations